Walking on Gender Tightrope With Multiple Marginalities: Asian International Female Students in STEM Graduate Programs - Lim, Jae Hoon; Wang, Yi; Wu, Tong; Li, Zhi; Sun, Ting (Journal of International Students, 2021)
This phenomenological research explored how Asian female international students (AFISs) understand the role of gender in their program experiences and how they cope with the challenges derived from their multiple marginalities—gender, foreign nationality, and race/ethnicity. Based on in-depth interviews with 21 Asian female international graduate students enrolled in various science, technology, engineering, and mathematics (STEM) disciplines, we analyzed the ideological undercurrents embedded in their genderblind perspectives and examined their coping strategies in the context of STEM disciplines. Our thematic findings illustrate the participants’ multiple marginalities as manifested in the concept of “gender advantage,” and the precarious power dynamics and ironic coping strategies that they adopt in undergraduate teaching contexts. This study suggests that STEM educators in higher education understand the multifaceted struggles of AFISs who inevitably embody multiple marginalities in their graduate programs and provide culturally relevant support and advocacy-based professional mentoring.